Ανάπτυξη εργαλείου για την τύχη πετρελαιοκηλίδας. Μελέτη και παραδείγματα. - Παρίσος, Φώτιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Μελέτης Πλοίου και Θαλάσσιων Μεταφορών, 2015)
The last 40 years the maritime world has seen thousands of oil spill accidents. The transport of oil by tankers for commercial purposes and the large number of coastal transport and storing facilities result in releasing significant quantities of oil into the seas and coasts. On the other hand, the impacts of oil spills at sea are multiple and their environmental costs depend on the type of oil and the ecosystem that will affect. Moreover, there are multiple physical, chemical and biological changes that take place from the time oil enters the sea and as long as it stays. In this context, the subject of this thesis was to upgrade the preexisting SpillSolver program, which is a tool that extracts results and graphs results for the main aging processes of an oil spill. Thus, the aim was to find new fate and aging models and parameters of oil spills and include them in the existing code, in order to provide a more comprehensive study of the phenomenon. The importance of these aspects is that, although they may not have a direct impact on aging, are very important, because their impact on environmental contamination is enormous. Finally, through our literature survey, ways of response countermeasures with accidental oil spills were proposed.